Enhancing Students’ Creative Thinking through Visual Arts in Higher Education - Sohibova Zuhroxon Akmal qizi (O‘RTA OSIYODA IJTIMOIY VA GUMANITAR TADQIQOTLAR, 2025)
Abstract: This article explores the role of visual arts, particularly painting, in developing students’ creative thinking and aesthetic perception in higher education. The study examines pedagogical approaches, interactive methods, and project-based learning to foster students’ creativity. It emphasizes the importance of practical exercises, peer evaluation, and technology integration in the educational process.